Trajectory sonar perception in the Ligurian Sea - Rikoski, R; Leonard, J; Newman, P; Schmidt, H (2006)
This paper describes a new technique for tracking locally curved unknown objects using sonar. The approach explicitly accounts for relevant robot dynamics. Objects are tracked by looking for temporal sequences of observations that fit a kinematic model. The method is illustrated using data from a synthetic aperture sonar gathered by an Odyssey III at NATO SACLANT's GOATS 2002 experiment in the Ligurian Sea. © Springer-Verlag Berlin/Heidelberg 2006.